2019
DOI: 10.1002/ptr.6518
|View full text |Cite|
|
Sign up to set email alerts
|

The effects of grape seed extract on glycemic control, serum lipoproteins, inflammation, and body weight: A systematic review and meta‐analysis of randomized controlled trials

Abstract: The aim of this systematic review and meta-analysis was to analyze the effects of grape seed extract (GSE) on glycemic control and serum lipoproteins, inflammation and body weight. Two independent authors systematically searched online databases including EMBASE, Scopus, PubMed, Cochrane Library, and Web of Science from inception until May 30, 2019. Cochrane Collaboration risk of bias tool was applied to assess the methodological quality of included trials. The heterogeneity among the included studies was asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 41 publications
0
33
1
Order By: Relevance
“…Only a reduction in body weight was observed in the animals supplemented with 1% GSE at one day of age (D group of animal). In humans, a recent meta-analysis on five studies showed no significant effect on body weight after a treatment with GSE [44]. The species but also the concentration of GSE, the manner of administration (mixed with the diet and free access or gavage (intragastric administration) and the dose used and the time of supplementation could explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Only a reduction in body weight was observed in the animals supplemented with 1% GSE at one day of age (D group of animal). In humans, a recent meta-analysis on five studies showed no significant effect on body weight after a treatment with GSE [44]. The species but also the concentration of GSE, the manner of administration (mixed with the diet and free access or gavage (intragastric administration) and the dose used and the time of supplementation could explain this discrepancy.…”
Section: Discussionmentioning
confidence: 99%
“…Management of ox‐LDL, as a common oxidative marker, points out the probable role of GSE in modification of oxidative stress through scavenging free radicals (Da Silva, Darmon, Fernandez, & Mitjavila, 1991; Natella, Belelli, Gentili, Ursini, & Scaccini, 2002). A recently published meta‐analysis put human trials together to reach a conclusion on the effects of GSE supplementation on serum lipoproteins (Asbaghi et al, 2020). They found a significant decrease in TC, LDL‐C and TG further highlighting the lipid‐modification role of GSE supplementation, although their findings are not in line with ours with regard to the increase in HDL‐C.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when comparing the efficacy, safety and quality of marketed herbal dietary supplements with pharmaceutical sector, the gap in the regulation system still serves as an unmet need (Williamson, Liu, & Izzo, 2020). On the other hand, while many available herbal products might be ineffective, GSE supplementation is not reported to have any unwanted or adverse impact and could be recommended as a potentially safe and efficient supplementation specially for individuals with obesity‐associated metabolic disorders (Asbaghi et al, 2020; Parandoosh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Grape seed extracts (GSEs) containing variable amounts of polyphenols and so-called oligomeric proanthocyanidins (PACs) have been investigated in several health conditions, including cardiovascular diseases (CVDs) prevention, chronic venous insufficiency (CVI) management, type 2 diabetes. Several clinical studies are now available, depicting their efficacy [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%